PENGARUH MODEL PEMBELAJARAN WIMBA TERHADAP BERPIKIR KREATIF PESERTA DIDIK PADA SUB KONSEP SISTEM REPRODUKSI (Studi Eksperimen di Kelas XI MIPA SMA Negeri 3 Tasikmalaya Tahun Ajaran 2016/ 2017) - Ramdhani, Fajar (LP3MPM Universitas Siliwangi, 2019)
The purpose of this research is to know the influence of Wimba model support to creative thinking on reproduction system sub concept. This research was conducted in December 2016 until June 2017. The research methode use true experiemntal design with population all of grade XIth Math-Science Senior High School 3 Tasikmalaya City. The sample used 2 classes taken by cluster random sampling that is class XI Sains 4 as experimental class and class XI Math-Science 5 as control class. The instrument used in research is the test figural creative on reproduction system sub concept which consist 8 item. To analyze data use t-test with signification value (?) 0,05 = 5%. The result of the research can be concluded is influence of wimba model support to creative thinking on reproduction system sub concept in class XI Math-Science Senior High School 3 Tasikmalaya City academic year 2016/2017